IMPLEMENTASI BAHASA JURNALISTIK PADA PEMBERITAAN HUKUM DAN KRIMINAL PORTAL BERITA WWW.GORIAU.COM - Septyana Yundri; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
GoRiau.com news portal is one of the most active news portal in Riau. This news portal has a readership of 200 thousand people a day and has been registered in the Press Company (SPS) with Card Number Member (KTA) 001/06 / E / 2014. News writing uploaded this news portal is guided by the rules of journalism language. Language is a means of conveying information. The use of good and correct language can make it easier for audiences to absorb information from the news clearly. In accordance with the assumption of Social Responsible Pers theory, where the press is required to be responsible for writing or news to the public. The purpose of this study is to know the standard systematic news writing applicable in the news portal GoRiau.com and the application of journalistic language on the news and criminal news portal GoRiau.com.This research uses qualitative research method. The location of this research is a news portal address at Surya Kartama Agung Street 44a Marpoyan Damai Pekanbaru. Selection of informants was done by purposive technique. As for the informants in this research is one person chairman of Persatuan Journalist Indonesia (PWI) Pekanbaru, one chief editor, one journalist, and two readers of GoRiau.com news portal. Data collection techniques used during the research is by way of observation, interview and documentation. While the data validity that writer use is triangulation.The results show that, GoRiau.com news portal does not have a specific systematic standard of news writing. The systematic standards used today follow a general rule that is also used by other mass media. The general rules are like following the Enhanced Spell (EYD), Great Language Dictionary (KBBI), Journalistic Language and the Journalistic Code of Ethics. As for the application of journalistic language in the rubric of Law and Criminal, the author finds the existence of news writing that does not match the rules of journalistic language guidelines applicable among journalists. In principle, news should be written following the principle of journalistic language is clear, solid, straightforward, interesting so that readers can understand it easily.Keywords: News portal, Journalistic language, GoRiau.com